2019
DOI: 10.1177/2158244019894278
|View full text |Cite
|
Sign up to set email alerts
|

An Enlightened Environment? Workplace Bullying and Incivility in Irish Higher Education

Abstract: This study explores the experiences of workplace ill-treatment of academic staff in the Irish Higher Education sector, with a focus on organizational response to experienced or witnessed workplace bullying and/or incivility. Workplace bullying is a significant problem, affecting approximately 15% of the workforce, with considerable variation by sector. Educational workplaces typically display prevalence rates that exceed average workplace bullying rates. The negative impacts on health and well-being are well d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 76 publications
(100 reference statements)
0
19
0
Order By: Relevance
“…More emphasis has to be placed during dignity and respect training in the academy about what constitutes authentic inclusion for neurodiverse students with TBI and for disability in general. There is clearly a long way to go before more accountability for one's actions within the academy becomes an expected norm [1,6], but such accountability is essential if neurodiverse students are to be given opportunities to be successful as students, future scholars and colleagues in the academy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More emphasis has to be placed during dignity and respect training in the academy about what constitutes authentic inclusion for neurodiverse students with TBI and for disability in general. There is clearly a long way to go before more accountability for one's actions within the academy becomes an expected norm [1,6], but such accountability is essential if neurodiverse students are to be given opportunities to be successful as students, future scholars and colleagues in the academy.…”
Section: Discussionmentioning
confidence: 99%
“…Incivility may also include interrupting/cutting people off while speaking, intentionally misinterpreting a person's instructions and undermining their credibility in front of others. These actions have negative impacts on those who are on the receiving end of uncivil behavior [6]. Incivility is often prompted by thoughtlessness, and those who behave uncivilly often claim that their intentions were misunderstood by a target, stating it was not meant to be hurtful.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying is associated with an organisational culture that does not have appropriate avenues of redress and therefore 'blind-eyes' bullying; where managers feel that they have support, at least implicitly, to mistreat their staff [24]; where the personal 'costs' of doing so are low, or worse, even rewarded [15]; and where there is a high level of competition within the workforce [25]. These conditions that provide a culture in which interpersonal bullying can flourish have been argued to be present in universities, and to be linked to the encroaching neoliberalisation of universities, and we build here on this previous work [20,26,27].…”
Section: Institutional Bullyingmentioning
confidence: 90%
“…There is evidence that bullying is more prevalent in universities generally, compared to many other sectors or industries [18]. Studies of bullying in Irish universities provide evidence of micro-political behaviours grounded in toxic academic culture, poor organisational responses and a failure to address complex power relations [19][20][21]. Poor experiences of leadership in Irish HEIs have been cited as leading to profoundly damaging experiences, including adverse physical and psychological impacts, repercussions for career trajectory, and fear.…”
Section: Institutional Bullyingmentioning
confidence: 99%
“…For example, although there are also opponents of the CSR concept (e.g., [24]), some studies have shown that CSR plays a positive role in building communal relationships between the organisation and its employees [25], stimulates positive emotions in employees [26], and is generally associated with a more favourable psychological climate inside the organisation [3]. Conversely, troubles in organising internal processes turn into a factor provoking workplace mobbing or creating conditions for its escalation [27][28][29][30][31][32]. Therefore, it could be predicted that inclusion of social responsibility in the organisational agenda should be of service to the greater well-being of employees and reduce the opportunities of such dangerous phenomenon as workplace mobbing.…”
Section: Introductionmentioning
confidence: 99%